QUALITY OF ECONOMIC SPACE: MEASUREMENT PROBLEMS AT THE MESO-LEVEL - A. A. Urunov; L. F. Levina; V. A. Ostapenko (Вестник университета)
The research of theoretical and methodological issues of assessing the quality of the economic space of Russian regions has been conducted. The concepts of economic space and its quality, institutional environment of economic space have been substantiated. In order to determine the integral indicator of the standard of living and the quality of the economic space, the method of a systematic approach has been applied, which allowed the authors to justify and identify the system-forming indicators of the quality of the ec onomic space and the features of the relationship between them. The developed method of assessing the quality of economic space at the meso-level allows you to form a rating of investment attractiveness of the subjects of the Federation and determine the integral indicator of the quality of life of the population of the regions. The results of the study can be used in the development of investment rating and typology of Russian regions, implementation of social policy and state regulation of spatial development.